2018
DOI: 10.1007/s11356-018-2629-3
|View full text |Cite
|
Sign up to set email alerts
|

Wetlands for wastewater treatment and subsequent recycling of treated effluent: a review

Abstract: Due to water scarcity challenges around the world, it is essential to think about non-conventional water resources to address the increased demand in clean freshwater. Environmental and public health problems may result from insufficient provision of sanitation and wastewater disposal facilities. Because of this, wastewater treatment and recycling methods will be vital to provide sufficient freshwater in the coming decades, since water resources are limited and more than 70% of water are consumed for irrigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(158 citation statements)
references
References 192 publications
(345 reference statements)
3
149
1
5
Order By: Relevance
“…Conversely, the River Mun ICW had a mean HRT of just 3.1 days, thus below the recommended period, because of a comparatively high outflow rate (187.1 m 3 /day) relative to the total volume (580 m 3 ). Previous studies have reported poor phosphorus removal performance when HRTs are short because of insufficient contact time between the sewage effluent and the sediments limiting phosphorus sorption and deposition (Almuktar et al, 2018); however no evidence of this was detected here. The HLR was also higher (0.055 m/ day) than recorded at the River Ingol ICW, although it was still below the recommended maximum of 0.1 m/day.…”
Section: Hydraulic Residence Times and Loading Ratescontrasting
confidence: 88%
See 1 more Smart Citation
“…Conversely, the River Mun ICW had a mean HRT of just 3.1 days, thus below the recommended period, because of a comparatively high outflow rate (187.1 m 3 /day) relative to the total volume (580 m 3 ). Previous studies have reported poor phosphorus removal performance when HRTs are short because of insufficient contact time between the sewage effluent and the sediments limiting phosphorus sorption and deposition (Almuktar et al, 2018); however no evidence of this was detected here. The HLR was also higher (0.055 m/ day) than recorded at the River Ingol ICW, although it was still below the recommended maximum of 0.1 m/day.…”
Section: Hydraulic Residence Times and Loading Ratescontrasting
confidence: 88%
“…Typically consisting of a series of interconnected ‘cells’ or pools, ICWs are unlined, free surface flow systems characterised by shallow water depths (~20–40 cm), emergent vegetation and a bed constructed from in situ soil rather than artificial liners as typically found in non‐integrated constructed wetland designs (Harrington et al ., 2007; Kadlec et al ., 2010). ICWs are planted with a range of native aquatic plants which support diverse periphyton communities that act as important biofilters, absorbing excess nutrients from sewage effluent and reducing water velocities to encourage sedimentation of entrained particulate material (Almuktar et al ., 2018; Cooper et al ., 2019). With the additional aim of enhancing biodiversity and ‘integrating’ into the local environment, ICWs are designed to be environmentally sustainable, robust and largely self‐managing, thus making them a cost‐effective pollution mitigation option (Scholz et al ., 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of nitrates, phosphates and heavy metals (Ni, Cd, Cr, Zn, Cu, Pb) in effluent leachates after passing through the reed plant filters was also highlighted, but their rate of abatement does not exceed 75%. These results appear to be an interessant alternative for the treatment of industrial wastewater by filters planted [41] with Phragmites australis (Cav) Trin ex Steud, Typha latifolia L. and Cyperus papyrus L. even though the salinity related to the nature of the wastewater somewhat reduces their purification capacity over time. However, we need to achieve absorption isotherms by the different plants and their kinetics of extraction of heavy metals to confirm the hypperaccumulator nature of the 3 plants chosen in this study.…”
Section: Resultsmentioning
confidence: 93%
“…It is demonstrated that the phenomenon of treatment is related to sedimentation, adsorption, biotic processing, and nutrient retention (20). However, an increase in HRT implies that the increase of the surface area of the gravel and, as a result, a larger total root surface area is available to support aerobic bacteria.…”
Section: Discussionmentioning
confidence: 99%